The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3892/mmr.2012.1163
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three methods for the detection of Epstein-Barr virus in Hodgkin’s lymphoma in paraffin-embedded tissues

Abstract: The percentage rate of Epstein-Barr virus (EBV)-positive cases of Hodgkin's lymphoma (HL) ranges between 20 and 70% in various studies worldwide. To further explore the definite rate in China, three methods, including immunohistochemistry for EBV latent membrane protein 1 (LMP1), in situ hybridization (ISH) for EBV-encoded RNA (EBER)-1 and polymerase chain reaction (PCR) for EBV BamHI‑W fragment, were employed to detect EBV in 59 cases of HL in China using paraffin-embedded tissue samples. Our results revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 16 publications
1
18
0
2
Order By: Relevance
“…EBER-ISH assay localizes EBV in biopsy tissue [1] • A biopsy assessed by EBER-ISH is needed to confirm each diagnosis and its relation to EBV We do IHC for EBV and recommend best practice of doing both in positive case so as to increase detection and association as the sensitivity and specificity in our study were 91% and 94%, respectively, which matched with the results demonstrated by Qi et al [5] which states to perform at least two methods to be performed for accurate results it also states that PCR is the most sensitive of the three methods, but it is unable to provide specific information with regard to the localization of EBVpositive cells which is possible in EBER and EBV by IHC.…”
Section: Discussionsupporting
confidence: 86%
“…EBER-ISH assay localizes EBV in biopsy tissue [1] • A biopsy assessed by EBER-ISH is needed to confirm each diagnosis and its relation to EBV We do IHC for EBV and recommend best practice of doing both in positive case so as to increase detection and association as the sensitivity and specificity in our study were 91% and 94%, respectively, which matched with the results demonstrated by Qi et al [5] which states to perform at least two methods to be performed for accurate results it also states that PCR is the most sensitive of the three methods, but it is unable to provide specific information with regard to the localization of EBVpositive cells which is possible in EBER and EBV by IHC.…”
Section: Discussionsupporting
confidence: 86%
“…Although EBV is a well-known risk factor for HL in endemic regions of the world, frequency of its association in our population has not been widely studied. There are various methods of detecting EBV in HL including immunohistochemistry (IHC), in situ hybridization (ISH), and polymerase chain reaction (PCR) [9]. EBV-infected tumor cells express a subset of EBV genes including latent membrane protein 1 (LMP1), LMP2a, EBV nuclear antigen 1 (EBNA1), EBV small nuclear RNA transcripts (EBER), and the BamHI A region transcripts [10–12].…”
Section: Introductionmentioning
confidence: 99%
“… Methodology (PCR versus in situ hybridization): we used a sensitive method for detection of EBV DNA with positive and negative controls. Based on the previous studies, PCR is as sensitive as in situ hybridization [ 20 , 21 ]. However, as we did not use in situ hybridization, we could not localize the exact infected cell with EBV in our controls which might be the circulating B cells of the skin instead of keratinocytes.…”
Section: Discussionmentioning
confidence: 99%